Nanocrystalline 6061 Al Powder Fabricated by Cryogenic Milling and Consolidated via High Frequency Induction Heat Sintering - Walid Hanna; Khinlay Maung; Ehab A. El-Danaf; Abdulhakim A. Almajid; Mahmoud S. Soliman; Farghalli A. Mohamed (Advances in Materials Science and Engineering)
Nanocrystalline 6061 Al alloy was synthesized by cryogenic milling (cryomilling). Both transmission electron microscopy and X-ray diffraction were used to monitor the change in grain size as a function of milling time. The results of both techniques demonstrated a close agreement with respect to two observations: (a) during cryomilling, the grain size of 6061 Al decreased with milling time, and (b) after 15 h of milling, the grain size approached a minimum value of about 22 nm. Despite this agreement, there was a discrepancy: for grain sizes > 40 nm, the grain size measured by transmission electron microscopy was appreciably larger than that inferred from X-ray diffraction. It was shown that powders consolidated via high frequency induction heat sintering (HFIHS) at 500 and 550°C maintained close to nanoscale grain sized microstructure in addition to high compact density in bulk samples. This was manifested by high strength values as compared to microscale grain samples.